Dengue infection in North India: An experience of a tertiary care center from 2012 to 2017 - Dinkar, Anju (Tzu Chi Med J, 2019)
OBJECTIVE: Recently, an alarming rise of dengue has been seen in India which remains a major public health concern. This study has been designed for a comprehensive overview of the epidemiology, gender, age, area distribution, symptomology, and seasonal variability. MATERIALS AND METHODS: Retrospective analysis of 900 suspected dengue cases of all age groups of either sex from 2012 to 2017 at a North Indian tertiary care hospital revealed 461 (51.22%) cases seropositive for dengue. RESULTS: The age group of 20–30 years was the most affected group with male predominance. The urban population was more affected as 75.05%, and maximum cases were detected in October month followed by November. Common abnormal laboratory parameters were thrombocytopenia (99.1%), hepatic dysfunction (59%), and leukopenia (26.68%). Two uncommon findings, pancytopenia and pancreatic dysfunction were reported in 7 and 3 cases respectively. CONCLUSION: Dengue infection in India has evolved rapidly, and regular outbreaks have been observed with a changing epidemiology, as the disease is rapidly spreading from urban to rural areas with increasing atypical manifestations.